Furfural equivalent (FE) determination in brewing - Savel, Jan; Pazourek, Karel (BrewingScience, 2001)
Continous flow analyser equipped with distillation unit, quartz flow cell and 275 nm UV detector was used for furfural equivalent (FE) value determination. The FE value comprises both furfural and other volatiles absorbances expressed in furfural concentration (μg.l⁻¹). The FE value is connected to sugar degradation, Maillard reaction and sensory active compound formation during food and beverage storage. The FE value can also be used as an indicator of brewing process consistency and for beverage ageing checking-up.